Football clubs’ social awareness as a leading strategy for performance: A fan token-based panel data analysis - Julen Castillo-Apraiz; Raúl Gómez-Martínez; Jesús Manuel Palma-Ruiz (Management Letters/Cuadernos de Gestión)
This paper analyses the extent to which football clubs’ emotional value —fan token-based— is related to economic value—share-based. Specifically, this research investigates the relationship between fan tokens and stock prices in European football clubs, aiming to discern fan engagement’s impact on financial market dynamics. We posit that fan token values are significantly linked to the valuation of clubs’ stocks. To assess this, a panel data analysis employing econometric models is conducted on six prominent football clubs that regularly participate in European competitions. The study period covers comprehensive data on fan token values and stock prices from 2022-2023. The findings reveal a positive and statistically significant correlation between fan token evolution and stock price movement. Individual ordinary least squares (OLS) regressions further confirm this trend. Moreover, a long/short strategy backtest emphasizes the substantial relationship between fan token evolution and stock performance. Hence, we demonstrate that clubs’ emotional perceptions —for which sustainability plays a key role— help predict clubs’ economic results. In other words, we demonstrate that being socially responsible is a strategy that could lead clubs to obtain a competitive advantage by improving fans’ perceptions, which in turn would have a positive impact on clubs’ performance. This study sheds light on the potential influence of fan engagement on football clubs’ financial market standing, offering insights crucial for stakeholders navigating the intersection of sports and finance.